2017
DOI: 10.1080/07420528.2016.1265979
|View full text |Cite
|
Sign up to set email alerts
|

Amerindian (but not African or European) ancestry is significantly associated with diurnal preference within an admixed Brazilian population

Abstract: Significant questions remain unanswered regarding the genetic versus environmental contributions to racial/ethnic differences in sleep and circadian rhythms. We addressed this question by investigating the association between diurnal preference, using the Morningness-Eveningness questionnaire (MEQ), and genetic ancestry within the Baependi Heart Study cohort, a highly admixed Brazilian population based in a rural town. Analysis was performed using measures of ancestry, using the Admixture program, and MEQ from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
2
1
0
3
Order By: Relevance
“…The ancestry estimation in SLE patients and healthy individuals based on a set of 345 SNP‐AIMs showed that both groups had major European ancestral contributions, followed by African and Amerindian (Figure ). This finding is consistent with the ancestral composition of Southeastern Brazilian population that exhibited 60–80% of European contribution followed by minor contributions from African and Amerindian ancestral populations (Ferreira et al., ; Muniz et al., ; Pena et al., ; Rolim et al., ; Egan et al., ).…”
Section: Discussionsupporting
confidence: 84%
“…The ancestry estimation in SLE patients and healthy individuals based on a set of 345 SNP‐AIMs showed that both groups had major European ancestral contributions, followed by African and Amerindian (Figure ). This finding is consistent with the ancestral composition of Southeastern Brazilian population that exhibited 60–80% of European contribution followed by minor contributions from African and Amerindian ancestral populations (Ferreira et al., ; Muniz et al., ; Pena et al., ; Rolim et al., ; Egan et al., ).…”
Section: Discussionsupporting
confidence: 84%
“…First, our analyses only employed data from individuals of European ancestry. Given that previous studies have highlighted ethnic differences in sleep-related traits, [61][62][63][64] the generalizability of the results may be limited. Also, the GCP estimates are tied to the statistical power of the GWAS, limiting the capacity to identify causal effects for some traits.…”
Section: A Negative Association Between the Ease Of Getting Up In Thementioning
confidence: 95%
“…The ancestry estimation in SLE patients and healthy individuals based on a set of 345 SNP-AIMs showed that both groups had major European ancestral contributions, followed by African and Amerindian (Figure 2). This finding is consistent with the ancestral composition of the Brazilian South-eastern population that exhibited 60─80% of European contribution followed by minor contributions from African and Amerindian ancestral populations (Egan et al, 2017, Ferreira et al, 2006.…”
Section: Discussionsupporting
confidence: 90%
“…A estimativa de ancestralidade em pacientes com LES e indivíduos saudáveis com base no conjunto de 345 SNP-AIMs mostrou que ambos os grupos tiveram maior contribuição ancestral europeia, seguida por africana e ameríndia. Esse achado é consistente com a composição ancestral da população do Sudeste brasileiro que apresenta 60-80% de contribuição europeia, seguida de menores contribuições africana e ameríndia(Egan et al, 2017; Embora em ambos pacientes e controles a contribuição europeia tenha sido a principal, foram detectadas diferenças significativas nas ancestrais europeias e africanas entre os dois grupos. Os pacientes com LES apresentaram maior contribuição africana (22%) do que os indivíduos saudáveis (13%), enquanto os controles mostraram uma contribuição europeia 12% maior do que os pacientes com LES.…”
unclassified